The Pentecostal prosperity gospel in Nigeria: paradoxes of corruption and inequality - Smith, Daniel Jordan (The Journal of Modern African Studies, 2021)
Preachers of the prosperity gospel in Nigeria criticise politicians’ greed and government corruption, even as many church leaders amass great wealth themselves. Drawing on ethnographic research, this article explores the relationship between Pentecostalism's prosperity gospel and political culture in Nigeria, especially as it pertains to problems of inequality and corruption. The analysis builds on a case study of one particular prosperity church in the city of Umuahia. It addresses the paradox that this brand of Pentecostalism articulates widespread discontent with the venality plaguing national political culture, while at the same time offering divine justification for the pursuit and accumulation of wealth. Examining not only Pentecostals’ interpretations of corruption, but also people's responses to scandals within these churches, the paper attempts to understand why Nigerians who are so aggrieved about corruption and inequality are at the same time drawn to churches that appear to reproduce many of the same dynamics.
free
Keywords: Nigeria; Pentecostal Christianity; corruption; inequality; prosperity gospel